Reconstructing the Phonology of Jakun Language Vowels: A Diachronic Phonological Analysis with Proto-Malay (Jurnal Bahasa, 2022)
This study discusses the Jakun language spoken by the Jakun Orang Asli community in the state of Johor. The objective of this study is to describe the process of vowel phonology of the Jakun language by comparing it with the process of vowel phonology of the Proto-Malay language that has been reconstructed by Adelaar (1992). This diachronic comparison is done to get the true phonological form of the Jakun language. This objective was achieved by using the rule ordering theory by Chomsky and Halle (1968). Next, this study uses a descriptive qualitative method to describe the collected field data. The results of this study have shown the true form of vowel phonology of the Jakun language in the state of Johor. Among the new findings of this study is the rejection of the statement by Carey (1976), who considers that the Jakun language has now lost its original nature and borrows Malay vocabulary only. This study has also found that the Jakun language does not borrow from the Malay language, but it is one of the branches of the Malay language, namely the Proto-Malay language. In addition, one of the new findings in this study is that there are vowels in the Jakun language that became nasal due to the process of regressive vowel induction. This phenomenon is considered special because the vowels in the closed syllable before the nasal and pharyngeal consonants at the end of the word receive nasal features from the nasal and pharyngeal consonants backwards. The existence of this regressive vowel origin can be said to be a new discovery in this study because this phonological process does not occur in standard Malay yet exists in other dialects, such as the Pattani Gerik dialect. The results of this study are expected to be a starting point for more research on the Jakun language elsewhere and on other Orang Asli languages.Keywords: Jakun aborigines, phonological reconstruction, vowel, Proto-Malay language, native language, historical linguisticsFull text: PDF